Design and experiment of advanced air balancing methods in air duct systems - Tok, You Xuan (Nanyang Technological University, 2020)
Energy conservation is critical for a region that seeks huge energy demand growth in the near future. BCA aims that 80% of Singapore’s commercial and public buildings to be energy efficient. With air duct system consuming more than 50% of the energy in commercial buildings, air balancing plays an important role to increase the system’s efficiency. Traditional air balancing is time consuming and has low accuracy which is affecting the performance of the air duct system. A novel air balancing method was proposed by NTU research group, eliminating the traditional TAB recursive procedure and having high accuracy results. This project implemented and performed calibration of the proposed air balancing method on 200mm diameter duct, formulated 2 models that describes the duct’s flow characteristic, with discrete model having an accuracy of 3.2864%, and continuous angle model having an accuracy of 9.4388%.